(untitled) (Al-Farooq Journal of Sciences, 2026)
This study was conducted to determine the effects of feed contaminated with aflatoxin B1 (AFB1) on growth performance in Turkey. Sixty, ducks randomly divided into two groups of 3 replicates and were fed commercial feed uncontaminated or contaminated AFB1 at level 250 µg/kg. AFB1 contaminated feed significantly decreased the body weight, feed intake and increased feed conversion rate (p<0.05). The results revealed that the growth performance of the contaminated diet compared to controls diet, a significant weight loss was observed 13.95%, 7.9% and 5.97% in the third week. Feed intake was significantly decreased (p<0.05) with the group fed AFB1 compared with the control. The overall, decrease was 2.4% and 4.8% for the second and third week respectively. The feed conversion was increased significantly (P<0.05) in the second and third week with an average of 3.5% and 5.9% over the control group. The results therefore, ducks performance was negatively affected by AFB1 contamination in feed. This will confirm that AFB1 contamination in poultry feed causes heavy economic losses by lowering body weight gain and feed conversion. Therefore, lower levels of Aflatoxin in the poultry feeds should be required if all acceptable risk is to be avoided.